2018
DOI: 10.7866/hpe-rpe.18.4.3
|View full text |Cite
|
Sign up to set email alerts
|

Public Policies Influence on Fiscal Deficit in the EU-28: Common Correlated Effects Approach

Abstract: This paper empirically investigates heterogeneous effects of different public policies (health, educa tion, pension expenditure) on fiscal deficit in the circumstances when fiscal sustainability became questionable in EU economies. The research is based on the sample of EU-28 over the period 1995 2015. The empirical analysis is conducted within the econometric framework of heterogeneous, cross sectional dependent panels, using common correlated effects approach. According to the main findings of the paper, dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 35 publications
(50 reference statements)
0
3
0
Order By: Relevance
“…Although the sample covers a longer period of time and preparation phase for membership, the majority of the analyzed economies became members of the EU in 2004 (2004 for the Czech Republic, Cyprus, Estonia, Hungary, Latvia, Lithuania, Malta, Poland, Slovakia and Slovenia, 2007 for Bulgaria and Romania and 2013 for Croatia). Crosssection dependence is therefore expected, since the institutional design of the EU includes the common market, common agricultural policy, customs union, tax harmonization and finally monetary union for some of the emerging EU economies, which inevitably leads to connections, spill-over effects and dependencies between EU countries [51].…”
Section: Pooled Mean Group Vs Mean Group Estimator Resultsmentioning
confidence: 99%
“…Although the sample covers a longer period of time and preparation phase for membership, the majority of the analyzed economies became members of the EU in 2004 (2004 for the Czech Republic, Cyprus, Estonia, Hungary, Latvia, Lithuania, Malta, Poland, Slovakia and Slovenia, 2007 for Bulgaria and Romania and 2013 for Croatia). Crosssection dependence is therefore expected, since the institutional design of the EU includes the common market, common agricultural policy, customs union, tax harmonization and finally monetary union for some of the emerging EU economies, which inevitably leads to connections, spill-over effects and dependencies between EU countries [51].…”
Section: Pooled Mean Group Vs Mean Group Estimator Resultsmentioning
confidence: 99%
“…Author concluded that weak sustainability exists in the analyzed sample and emphasised advantages of methods for heterogeneous panel estimation. Josifidis et al (2018) as well emphasise the importance of heterogeneity in the sample of European Union economies, namely, the study provides evidence of heterogeneous effects of different public policies on fiscal sustainability in EU-28. On the other hand, Ehrhart and Llorca (2008) showed fiscal sustainability in six South-Mediterranean countries, while Campeanu and Andreea (2010) analyzed fiscal sustainability and fiscal reactions in Central and Eastern European countries, distinguishing economies which fiscal adjustments could improve the ability to run a primary surplus, from economies with opposite responses.…”
Section: Literature Reviewmentioning
confidence: 85%
“…Both the CS-ARDL and CCEMG estimators are equally efficient to produce reliable estimates in the presence of endogeneity, heterogeneity, and cross-sectional dependence. The representation of the CCEMG model according to Azam and Haseeb (2021), Josifidis et al (2018) is:…”
Section: Robustness Checks and Further Analysismentioning
confidence: 99%